Home Vegetable Garden Techniques: Hand Pollination of Squash and Corn in Small Gardens - Ed Thralls; Danielle Treadwell (EDIS)
HS-1149, a 4-page illustrated fact sheet by Ed Thralls and Danielle Treadwell, addresses techniques for hand pollination of squash and corn to produce bountiful harvests in home gardens. Includes references. Published by the UF Department of Horticultural Sciences, December 2008.